The relationship between stigma and alexithymia and their impact on satisfaction with care among people living with chronic obstructive pulmonary disease (COPD): A path analysis - Keya Bibikar; Sanduni Madawala; Claire Hutton; Anne E. Holland; Chris Barton (PLoS ONE, 2025)
Introduction Stigma is a common experience for individuals diagnosed with chronic obstructive pulmonary disease (COPD). It may elicit a set of emotional responses, consistent with alexithymia, that hinders conversations with healthcare providers. Alexithymia describes a set of cognitive-affective traits linked with difficulty identifying and distinguishing emotions. This study explored whether anticipated stigma in healthcare settings among patients with COPD is associated with alexithymia and whether it predicts satisfaction with care from healthcare providers. Methods An online survey comprising validated questions was distributed between May and June 2024 to individuals who self-reported a doctor-diagnosis of COPD. Participants were recruited from advertisements on social media, online COPD support groups, and previous related studies. Correlation and multiple linear regression analyses were conducted to examine relationships between variables. Structural equation modelling (SEM) was used to explore these relationships through path analysis. Results Respondents (n = 123) ranged in age from 33 to 90 years. Greater anticipated stigma was associated with higher levels of alexithymia (r = 0.278, p = 0.002) and lower satisfaction with care (r = −0.462, p < 0.001). In the path analysis, social support emerged as a mediating factor between alexithymia and anticipated stigma. As alexithymia increased, satisfaction with social support decreased, which was associated with higher anticipated stigma and reduced satisfaction with care from healthcare providers. Conclusion This study helps clarify the association between alexithymia and anticipated stigma among people with COPD and how this impacts satisfaction with care. The findings signal a need to raise awareness of alexithymia and implement interventions to reduce stigma and enhance social support resources.